What do community pharmacists do?: results from a work sampling study in London. (14th January 2014) - Davies, James E; Barber, Nicholas; Taylor, David
Abstract: Objective: Government and professional groups within the pharmacy have sought to extend the role of pharmacists from dispensing-focused towards the provision of further pharmaceutical services. The aim of this research was to describe how pharmacists in current English community pharmacy practice spend their time using a work sampling method. Methods: Ten community pharmacies across London were purposively selected. Trained observers visited one pharmacy each to record the activities of the responsible pharmacist, using a fixed-interval work sampling technique. Activities were recorded every minute, into one of 18 predefined, piloted and tested activity codes. Data were recorded for 4 h each day for 1 week at each pharmacy during 2011. Key findings: A total of 12 306 observations were recorded across the pharmacies. The pharmacists spent the majority of their time assembling and labelling products (median 25.2%; quartiles 19.0, 31.0) and monitoring prescriptions for clinical appropriateness (10.6%; 8.3, 13.0). The next most prevalent activity code was rest, waiting and breaks (8.6%; 6.9, 15.3). They spent more time offering non-prescription medicines advice (6.6%; 3.5, 7.6) than prescription medicines counselling (3.8%; 2.8, 5.6). The provision of pharmaceutical services accounted for 3.2% (0.8, 7.5) of pharmacists' time. Overall, 46.2 % (35.2, 56.2) of their time was spent on activities deemed to be 'Professional'. Conclusions: Despite repeated attempts during the last decade to shift pharmacists' roles towards patient-care activities, on the basis of this research, community pharmacists continue to spend the majority of their time on technical dispensing (as opposed to cognitive patient-centred) tasks.